Impact of Environmental Governance on the Relationship between Environmental Innovation and Level of CO2 Emissions - Amara, Tijani; Ahmadi, Ali (Journal of Environmental Accounting and Management, 2026)
This article examines the impact of the level of environmental innovation on CO2 emissions, and additionally the contribution of the moderating effect of environmental governance score in this relationship. Our findings are associated with a moderating effect of the environmental governance score from the sample of firms on the relation linked the environmental innovation and the CO2 emissions. Furthermore, the results show that environmental innovation associated with better environmental governance leads to a decrease in CO2 emissions. Our findings hold for subsamples of firms with strong/weak environmental governance and ESG performance. We also perform additional analyses and divide the sample into subsamples based on the eco-innovation score and the ESG and environmental governance score. The results show that the level of eco-innovation is important and negatively associated with carbon emissions for firms regardless of whether they have a high or low ESG score.